VOCABULARY MASTERY BY USING ENGLISH SONGS - Yuricki, Effrina (Universitas Halu Oleo, 2021)
This research attempts to investigate the improving students’ vocabulary mastery by using English songs at the Eighth Grade of SMP Negeri 2 Gunung Agung Tulang Bawang Barat. The method of this research was conducted by using the Classroom Action Research (CAR) method. The population of the research was 28 students. In this research, the writer took one class for the sample. The writer used observation and tests for the data collecting technique. The writer found that using English songs successfully improved students’ vocabulary mastery. It can be seen from the result of vocabulary activity and mastery. It was increased, from cycle I to cycle II by using English songs. In cycle II, the writer used the same technique but added a few different changes related to the problem in cycle I. The writer found that the average score in cycle I was 54.71, and students who passed the minimum criteria mastery was 46.42% and it increased in cycle II, the average score in cycle II was 73.78, and students who passed the minimum criteria mastery was 75%. Therefore, it can be concluded that this technique was successfully applied in improving students’ vocabulary activity and mastery at the eighth grade of SMP Negeri 2 Gunung Agung Tulang Bawang Barat.